Developing an alternative alcohol advertising complaint review system: lessons from a world-first public health advocacy initiative - Hannah L Pierce; Julia M Stafford; Mike Daube (Sax Institute, 2017)
Young people in Australia are frequently exposed to alcohol marketing. Leading health organisations recommend legislative controls on alcohol advertising as part of a comprehensive approach to reduce alcohol-related harm. However, Australia relies largely on industry self-regulation. This paper describes the development and implementation of the Alcohol Advertising Review Board (AARB), a world-first public health advocacy initiative that encourages independent regulation of alcohol advertising. The AARB reviews complaints about alcohol advertising, and uses strategies such as media advocacy, community engagement and communicating with policy makers to highlight the need for effective regulation. In 4 years of operation, the AARB has received more complaints than the self-regulatory system across a similar period. There has been encouraging movement towards stronger regulation of alcohol advertising. Key lessons include the importance of a strong code, credible review processes, gathering support from reputable organisations, and consideration of legal risks and sustainability. The AARB provides a unique model that could be replicated elsewhere.